Effects of statins on experimental colitis in normocholesterolemic rats - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2006)
Objective. The results of previous studies suggest that statins have a direct anti-inflammatory effect that is not directly related to their cholesterol-lowering activity. The aim of this study was to investigate the effect of simvastatin (SIM) and fluvastatin (FLU) on trinitrobenzene sulfonic acid (TNBS)-induced colonic inflammation in rats. Material and methods. The drugs were given for 3 days (0.1 and 1 mg/kg day(-1); intraperitoneally) after induction of colitis. The lesions in the distal colon were scored at the macroscopic and microscopic level. Tissue malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and collagen content were assessed and formation of reactive oxygen species and peroxynitrite was monitored by chemiluminescence ( CL) assay. Trunk blood was collected for the measurement of serum tumor necrosis factor (TNF)-alpha level. Results. Treatment with SIM reduced the lesion score of the colitis group at macroscopic level (p < 0.05), but there was no effect of treatment with FLU. The increase in colonic MDA level of the colitis group was reduced by both drugs at all doses (p < 0.05-0.001). The decrease in GSH and the an increase in MPO activity in the colitis group were reversed by SIM at all doses (p < 0.01), but FLU had no effect. An increase in colonic lucigenin CL value in the colitis group was reduced by SIM and FLU at all doses (p < 0.001) and an increase in peroxynitrite ratio in the colitis group showed a significant reduction in SIM-treated groups; FLU reduced this effect at a dose of 1 mg/kg (p < 0.01). An increase in tissue collagen content and serum TNF-alpha level in the colitis group was reversed by both drugs at all doses (p < 0.001). Conclusions. SIM and FLU seemed to be beneficial in a TNBS-induced rat colitis model through the prevention of lipid peroxidation, superoxide generation, cytokine production and neutrophil accumulation.
Keywords: colitis; fluvastatin; oxidant; rat; simvastatin; HMG-COA REDUCTASE; INFLAMMATORY BOWEL-DISEASE; CORONARY-HEART-DISEASE; TRINITROBENZENE SULFONIC-ACID; OXYGEN METABOLITE PRODUCTION; IN-VITRO; REACTIVE OXYGEN; LOVASTATIN TREATMENT; CHOLESTEROL LEVELS; RANDOMIZED-TRIAL